Limited Effects of an eIF2αS51A Allele on Neurological Impairments in the 5xFAD Mouse Model of Alzheimer’s Disease - Katharina Paesler; Kan Xie; Moritz M. Hettich; Magdalena E. Siwek; Devon P. Ryan; Susanne Schröder; Anna Papazoglou; Karl Broich; Ralf Müller; Astrid Trog; Alexander Garthe; Gerd Kempermann; et al. (Neural Plasticity)
Alzheimer’s disease (AD) has been associated with increased phosphorylation of the translation initiation factor 2α (eIF2α) at serine 51. Increased phosphorylation of eIF2α alters translational control and may thereby have adverse effects on synaptic plasticity, learning, and memory. To analyze if increased levels of p-eIF2α indeed promote AD-related neurocognitive impairments, we crossed 5xFAD transgenic mice with an eIF2αS51A knock-in line that expresses the nonphosphorylatable eIF2α variant eIF2αS51A. Behavioral assessment of the resulting mice revealed motor and cognitive deficits in 5xFAD mice that were, with the possible exception of locomotor hyperactivity, not restored by the eIF2αS51A allele. Telemetric intracranial EEG recordings revealed no measurable effects of the eIF2αS51A allele on 5xFAD-associated epileptic activity. Microarray-based transcriptome analyses showed clear transcriptional alterations in 5xFAD hippocampus that were not corrected by the eIF2αS51A allele. In contrast to prior studies, our immunoblot analyses did not reveal increased levels of p-eIF2α in the hippocampus of 5xFAD mice, suggesting that elevated p-eIF2α levels are not a universal feature of AD models. Collectively, our data indicate that 5xFAD-related pathologies do not necessarily require hyperphosphorylation of eIF2α to emerge; they also show that heterozygosity for the nonphosphorylatable eIF2αS51A allele has limited effects on 5xFAD-related disease manifestations.